Mahmud Zamakhshari’s Contribution to Linguistics and His Scientific Legacy - Nuritdin qizi, Salimova Sitora-Bonu (Indonesian Journal Publisher, 2025)
This paper explores the linguistic significance and scholarly legacy of Mahmud Zamakhshari, one of the most prominent philologists of the Islamic Golden Age. Special attention is given to his influential lexicographic works, particularly Asas al-Balagha, which reflects his deep understanding of Arabic eloquence and grammar. The study analyzes the structure of his dictionary, the use of illustrative materials from the Qur’an, Hadith, Arabic poetry, and proverbs, as well as the categorization of lexical entries by meaning and usage. Furthermore, the paper highlights Muqaddimat al-Adab as a foundational work in multilingual lexicography and comparative linguistics. Zamakhshari's approach demonstrates a remarkable integration of linguistic theory and practical application, making his contributions valuable to both historical and contemporary linguistic studies.